The scinderin gene (SCIN) is the direct target of miR3085-3p in chondrocytes - Le, Linh T.T.; Ho, Phuong T.B.; Clark, Ian M. (Archives of Biological Sciences, 2020)
Paper description: Aberrant expression of miR-3085-3p is found in osteoarthritis (OA). Insight into its biological function could be useful for future miRNA-based therapy of OA. miRNA biological function can be dictated through its direct targets. Bioinformatic algorithms were employed to identify miRNA potential targets. The target was then verified experimentally. The gene scinderin (SCIN) is the direct target for miRNA-3085-3p in chondrocytes, the only cell in cartilage. MiR-3085-3p might play a role in OA at least in part through direct targeting of SCIN. Abstract: MiR-3085-3p was shown to play a crucial role in cartilage biology, with potential impacts in osteoarthritis (OA). Insight into this miRNA function could be of practical importance for future miRNA-based therapy, however, little is known regarding the biological roles of this miRNA. The physiologic function of an individual miRNA is dictated through its mRNA targets, and as SCIN (scinderin, also known as adseverin) was reported to be involved in chondrocyte differentiation, maturation, and phenotype maintenance, this study aimed to prove SCIN is a direct target of miRNA-3085-3p. Bioinformatics algorithms were utilized for predicting their interacting sites. Gain- and loss-of-function experiments with miRNA-3085-3p were performed and SCIN expression was measured by real-time RT-PCR. SCIN 3’UTR regions harboring either the miR-3085-3p seed site or its mutant version were cloned into pmirGLO downstream of a reporter firefly luciferase encoding gene. The effect of miR-3085-3p on this region was determined by the luciferase assay. Four binding sites of miR-3085-3p in SCIN 3’UTR were identified. SCIN expression level was found to be inversely correlated with the level of miRNA-3085-3p. MiR3085-3p directly binds to its binding sites in SCIN 3’ UTR. These data suggest that SCIN is the direct target of miR-3085-3p in chondrocyte cells. https://doi.org/10.2298/ABS200507031L Received: May 7, 2020; Revised: July 15, 2020; Accepted: August 1, 2020; Published online: August 24, 2020 How to cite this article: Le LT, Ho PT, Clark IM.The scinderin gene (SCIN) is the direct target of miR3085-3p in chondrocytes. Arch Biol Sci. 2020;72(3):373-8.